Pengaruh JII 70 Dan ISSI Terhadap Pertumbuhan Perekonomian Indonesia - Zaidah, Ghina Rizki; Widjiantoro, Surya Tegar (Jurnal Ilmiah Ekonomi Islam, 2025)
This research is based on the discrepancy between theory and facts found in the field, as well as inconsistent results from previous studies that serve as references in this study. The aim of this research is to analyze the influence of the Jakarta Islamic Index 70 (JII 70) and the Indonesian Sharia Stock Index (ISSI) on Indonesia's economic growth during the period of 2019-2023. The research method used is a quantitative approach with secondary data obtained from BPS, OJK, and investing web pages. The sample selection was done using purposive sampling technique, covering two sharia stock indices, namely JII 70 and ISSI. The partial test results show that JII 70 has a negative and significant effect on economic growth, while ISSI has a positive and significant effect. The simultaneous test indicates that overall, JII 70 and ISSI have a positive and significant impact on economic growth. The coefficient of determination of 95.7% indicates that these two variables can explain economic growth, while the remaining 4.3% is influenced by other factors.